2020
DOI: 10.3389/fimmu.2020.00953
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Thymic Output Can Be Related to the Low Immune Reconstitution and T Cell Repertoire Disturbances in Relapsing Visceral Leishmaniasis Associated HIV/AIDS Patients

Abstract: Silva-Freitas et al. Thymic Impairment in VL/HIV Patients Results: VL/HIV cases presented an altered mobilization profile (expansions or retractions) of the TCRVβ families when compared to HS independent of the follow-up phase (p < 0.05). TCRVβ repertoire on CD4 + T-cells was more homogeneous in the NR-VL/HIV cases, but heterogeneous on CD8 + T-cells, since different Vβ-families were mobilized. NR-VL/HIV had the inflammatory pattern reduced after 6 mpt. Importantly, VL/HIV patients showed number of TREC copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…In addition to bone marrow failure, reduced thymic output might also play a role in the low number of CD4 + T cells, and indeed, a recent study showed a clear correlation between decreased numbers of recent thymic emigrants and poor CD4+ T cell recovery in HIV patients (48). The study by Silva-Freitas et al also suggested that in VL/HIV co-infected patients who do not relapse, more new emigrant T cells can be detected that might contribute to the control of parasite replication (49). In addition to its potential contribution to the low levels of IFNγ produced in the WBA, a poor CD4 + T cell recovery is also associated with persistent immune activation and inflammation (50); that in turn contribute to higher risks of several morbidities, as well as death (51,52).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to bone marrow failure, reduced thymic output might also play a role in the low number of CD4 + T cells, and indeed, a recent study showed a clear correlation between decreased numbers of recent thymic emigrants and poor CD4+ T cell recovery in HIV patients (48). The study by Silva-Freitas et al also suggested that in VL/HIV co-infected patients who do not relapse, more new emigrant T cells can be detected that might contribute to the control of parasite replication (49). In addition to its potential contribution to the low levels of IFNγ produced in the WBA, a poor CD4 + T cell recovery is also associated with persistent immune activation and inflammation (50); that in turn contribute to higher risks of several morbidities, as well as death (51,52).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the thymus of patients living with HIV presents alterations in the lymphoid and stromal compartments as well as in the generation of the V-beta repertoire of T lymphocytes ( 183 ) that are typical of aging. In addition, HIV infection potentially contributes for the inflammatory immunopathogenesis of VL and, at the same time, impairs the effector immune responses to antigens, including Leishmania ( 184 ).…”
Section: Leishmaniasismentioning
confidence: 99%
“…Similar results were observed in VL/HIV coinfection [23]. This de cit in the recovery of CD4 + T lymphocytes can be related to an impaired input of cells originated from bone marrow, de cient replication rate or thymic dysfunction [24,[36][37]. Low CD4 + T cell counts in VL/HIV coinfected patients during the active phase of VL was a predictor of a poor prognosis: death or recurrence [38][39].…”
Section: Discussionmentioning
confidence: 53%